Biochemical and Computational Approach of Selected Phytocompounds from Tinospora crispa in the Management of COVID-19 - Ahmed Rakib; Arkajyoti Paul; Md. Nazim Uddin Chy; Saad Ahmed Sami; Sumit Kumar Baral; Mohuya Majumder; Abu Montakim Tareq; Mohammad Nurul Amin; Asif Shahriar; Md. Zia Uddin; Mycal Dutta; Trina Ekawati Tallei; et al. (Molecules, 2020)
A pandemic caused by the novel coronavirus (SARS-CoV-2 or COVID-19) began in December 2019 in Wuhan, China, and the number of newly reported cases continues to increase. More than 19.7 million cases have been reported globally and about 728,000 have died as of this writing (10 August 2020). Recently, it has been confirmed that the SARS-CoV-2 main protease (Mpro) enzyme is responsible not only for viral reproduction but also impedes host immune responses. The Mpro provides a highly favorable pharmacological target for the discovery and design of inhibitors. Currently, no specific therapies are available, and investigations into the treatment of COVID-19 are lacking. Therefore, herein, we analyzed the bioactive phytocompounds isolated by gas chromatography–mass spectroscopy (GC-MS) from Tinospora crispa as potential COVID-19 Mpro inhibitors, using molecular docking study. Our analyses unveiled that the top nine hits might serve as potential anti-SARS-CoV-2 lead molecules, with three of them exerting biological activity and warranting further optimization and drug development to combat COVID-19.